2014
DOI: 10.15809/irriga.2014v19n1p61
|View full text |Cite
|
Sign up to set email alerts
|

Ajuste E Aplicação Do Irrigâmetro No Manejo Da Água De Irrigação

Abstract: This study aimed to determine heights of water levels in the evaporimeter of the Irrigameter to directly obtain the evapotranspiration of the crop (ETc) in several stages of its growth. Moreover, evaluate the performance of the Irrigameter at managing irrigation in the bean cowpea crop. The study was conducted in the Campus of the State University of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
1
3
0
2
Order By: Relevance
“…Disagreeing with the present study, for the methods of Priestley-Taylor and Hargreaves-Samani, Guedes Filho et al (2011) and Silva et al (2012) observed a tendency of ETo underestimation in daily data for the city of Areia -PB and for the northern region of Recife -PE, respectively. On the other hand, Tagliaferre et al (2010) observed, for Eunápolia -BA, a behavior similar to that observed in this study, where the Hargreaves-Samani method showed a tendency of 23% overestimation of ETo data. Vallory et al (2016) also observed a tendency of overestimation of ETo data for the state of Rio de Janeiro, using the PriestleyTaylor and Hargreaves-Samani methods.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Disagreeing with the present study, for the methods of Priestley-Taylor and Hargreaves-Samani, Guedes Filho et al (2011) and Silva et al (2012) observed a tendency of ETo underestimation in daily data for the city of Areia -PB and for the northern region of Recife -PE, respectively. On the other hand, Tagliaferre et al (2010) observed, for Eunápolia -BA, a behavior similar to that observed in this study, where the Hargreaves-Samani method showed a tendency of 23% overestimation of ETo data. Vallory et al (2016) also observed a tendency of overestimation of ETo data for the state of Rio de Janeiro, using the PriestleyTaylor and Hargreaves-Samani methods.…”
Section: Resultssupporting
confidence: 90%
“…Tagliaferre et al (2010), in Eunápolis -BA and Uberlândia -MG, and Sanches et al (2015), in the northern region of Brazil, also found the Priestley-Taylor method to be of better performance among other methods used.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Figura 2 -Irrigâmetro instalado. No detalhe se observam a indicação da lâmina evapotranspirada (10,0 mm), o tempo de irrigação (3:00 h) e o momento de irrigar (cor amarela) 1 Disponível em: <http://irrigacerto.com.br/> Acesso em: out., 2015. De acordo com os resultados obtidos por Oliveira et al (2007a), Oliveira et al (2007b), Tagliaferre et al (2012) e Tagliaferre et al (2014), o Irrigâmetro pode ser usado para estimar a evapotranspiração de qualquer cultura, em qualquer estádio de desenvolvimento, para um valor de Kc (coeciente de cultura) desejado. Sendo assim, o uso do Irrigâmetro torna-se uma alternativa viável por ser de custo mais baixo que o tanque Classe "A" o lisímetro de pesagem e a estação meteorológica automática e, principalmente, por ser de fácil operação (OLIVEIRA et al, 2008a), a qual consiste simplesmente em abrir e fechar válvulas nele existentes, obedecendo a uma sequência predenida, além de apresentar simples montagem e desmontagem, o que facilita o transporte e a sua instalação no campo (GIOVANELLI, 2012).…”
Section: Figura 1 -Irrigâmetro E Seus Componentesunclassified